Identification and optimization of urban wetland ecological networks in highly urbanized areas: A case study of Haidian District, Beijing - Wang Zecheng; Zhao Xinsheng; Cui Lijuan; Lei Yinru; Guo Ziliang; Wang Jinzhi; Li Jing; Zhai Xiajie; Wang Rumiao; Li Wei (Ecological Indicators)
With the rapid development of urbanization, urban wetlands have been severely damaged by human activities and natural factors, leading to problems such as reduced area and decreased connectivity between wetlands. Constructing wetland ecological networks is an effective approach to alleviating urban wetland landscape fragmentation and enhancing wetland connectivity. However, research on constructing, analyzing, and optimizing wetland ecological networks in highly urbanized areas remains limited. This study used landscape ecology, topology, and spatial analyses techniques to build a wetland ecological network for Haidian District, a rapidly urbanizing area. A complex network model was used to conduct in-depth analysis and optimization of the network. The results show that the wetland ecological network in Haidian District identified 25 wetland ecological sources and 45 wetland stepping-stone patches. The network established 64 wetland ecological corridors and 87 wetland stepping-stone corridors. Additionally, 21 ecological fracture points and 15 high ecological barriers were detected in the network. Topological analysis revealed that removing key nodes would significantly reduce the stability of the network. To address this issue, a simulation was performed that added eight new corridors, resulting in improved overall connectivity and stability of the optimized wetland ecological network. Specific conservation and restoration strategies were proposed based on the existing issues of wetlands in Haidian District. The findings of this study provide important references for the sustainable development of the wetland ecosystem in Haidian District and offer methodological support for the conservation and restoration of wetlands in other highly urbanized areas.